Latencies to first interictal epileptiform discharges in different seizure types during video-EEG monitoring - Koc, Guray; Morkavuk, Gulin; Akkaya, Efdal; Karadas, Omer; Leventoglu, Alev; Unay, Bulent; Gokcil, Zeki (W B Saunders Co Ltd, 2019)
Purpose: Interictal epileptiform discharges (IEDs) have high diagnostic value concerning patients with epilepsy and the instances of obtaining IEDs increase with longer recording times. However, the merit of a single, extended electroencephalography (EEG) recording in detecting IEDs has not been substantiated. We aimed to determine the optimal duration of an EEG required to diagnose epilepsy in different seizure types. Methods: Overall, 84 patients-29 with generalised onset epilepsy and 55 with focal onset epilepsy were evaluated. Long-term video electroencephalographic monitoring (VEM) was analysed to find the first definite IED besides assessing the first seizure and latency. Results: The median latency of the first IED (12 min, ranging from 1 to 440 min vs. 55 min, ranging from 2 to 7500 min; p = 0.014) and the median duration of a VEM recording (2 d, ranging from 1 to 10 d vs. 3 d, ranging from 1 to 10 d; p = 0.012) were found significantly lower in the generalised epilepsy group compared with that in the focal epilepsy group. Conclusions: Generalised onset epilepsy showed a significantly shorter latency to IED and VEM duration compared with focal onset epilepsy. In our data set, all the patients with generalised onset epilepsy had interictal IED within 10 h, but the patients with focal onset epilepsy required monitoring for three days to obtain IED.
Keywords: Interictal epileptiform activity; Epilepsy, focal onset seizure; generalised onset seizure; Video-EEG monitoring